2021
DOI: 10.1097/ceh.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

An Interprofessional Group Intervention to Promote Faculty Well-Being: A Randomized Clinical Trial

Abstract: Introduction: To evaluate the effect on engagement, relational connection, and burnout of an intervention involving clinical faculty meeting in interprofessional self-facilitated groups and to determine whether a written discussion guide is necessary to achieve benefit. Methods: This is a randomized controlled trial, conducted at a large US academic medical center from May to August 2018. Subjects included 25 clinical physicians, nurse practitioners, and certified nurse midwives. The intervention involved thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This finding may represent a floor effect (which occurs when a large percentage of respondents score near the lower limit on a questionnaire). At baseline, the cohort had low GSI scores (median [IQR], 9 [4][5][6][7][8][9][10][11][12][13][14][15] points) and thus may not have been able to further reduce symptoms in a 3-month period. Only 3 participants in the TM group and 6 participants in the control group had a high standard GSI score (Ն63 points) at baseline, 49 and these small numbers were inadequate for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may represent a floor effect (which occurs when a large percentage of respondents score near the lower limit on a questionnaire). At baseline, the cohort had low GSI scores (median [IQR], 9 [4][5][6][7][8][9][10][11][12][13][14][15] points) and thus may not have been able to further reduce symptoms in a 3-month period. Only 3 participants in the TM group and 6 participants in the control group had a high standard GSI score (Ն63 points) at baseline, 49 and these small numbers were inadequate for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized clinical trials have evaluated strategies to reduce stress and burnout, such as the use of psychological or sensory-emotional techniques, [10][11][12][13] group discussions, 14,15 mindfulnessor compassion-based programs, [16][17][18][19] auricular acupressure, 20 and cannabidiol treatment. 21 These studies reported some short-term improvements; however, small cohorts, high attrition rates, lack of sample diversity, or the need for pharmacological therapy has limited their utility, highlighting the need for rigorously tested interventions for burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies investigating the scales of interest were excluded on the basis of either unclear methods (e.g. an inability to determine which of the two PRU scales or subscales were implemented due to discrepancies in scale naming and/or item numbers) 80,81 or a lack of data. 82 Study characteristics and MERSQI outcomes are provided in Appendix S1.…”
Section: Resultsmentioning
confidence: 99%
“…In a systematic review and meta-analysis of 15 randomized clinical trials of individual or organizational interventions (716 physicians) and 37 cohort studies (2914 physicians), the prevalence of burnout as assessed using the Maslach Burnout Inventory decreased from 54% to 44% in the intervention groups. In 1 trial, for instance, 3 monthly dinner meetings for physicians, nurses, and midwives decreased burnout and improved engagement, sense of connection to colleagues, and perceived department commitment to staff well-being . Good relationships with colleagues, meaningful interactions with learners, and protected time for personal life were crucial for full-time university hospital faculty .…”
Section: Discussionmentioning
confidence: 99%
“…In 1 trial, for instance, 3 monthly dinner meetings for physicians, nurses, and midwives decreased burnout and improved engagement, sense of connection to colleagues, and perceived department commitment to staff well-being. 27 Good relationships with colleagues, meaningful interactions with learners, and protected time for personal life were crucial for full-time university hospital faculty. 28 Facilitated small-group curriculum reduced depersonalization.…”
Section: Discussionmentioning
confidence: 99%